Strategi Pengembangan Kewirausahaan untuk Menciptakan Pelaku Usaha yang Kompetitif pada Kelompok UMKM Makanan dan Minuman di Daerah Gebang Kidul - Nada, Chumaida Qudrotul; Andayani, Sri; Maduwinarti, Ayun (Research Journal of Social Science and Economics, 2025)
UMKM or micro, small, medium enterprises are one of the drivers of economic development because they are considered more capable of surviving despite the economic crisis. The food and beverage stall business is currently showing very rapid development and competition. The obstacles faced by food and beverage UMKM in the Gebang Kidul area are in terms of increasing the number of consumers. Because the majority of consumers from UMKM in the village are students from the ITS, PENS and PPNS campuses. The purpose of this research is to find out and analyze the Entrepreneurship Development Strategy to Create Competitive Business Actors in the Food and Beverage UMKM Group in the Gebang Kidul Region. The type of research used in this research is to use a qualitative approach with the SWOT method. In qualitative research, the main characteristics come from the natural background / reality in the community, using qualitative methods with observation steps, interviews and SWOT analysis. Based on the results of this study, it shows that food and beverage SMEs in the Gebang Kidul area to develop competitive MSME actors have strengths and opportunities, so they can take advantage of existing opportunities. The strategy that can be applied in this condition is to support an aggressive growth policy (Growth Oriented Strategy). Keywords: UMKM, Development Strategy, Competitive